Relative energy deficiency in sport (RED-S) - Todd, E.; Elliott, N.; Keay, N. (British Journal of General Practice, 2022)
Relative energy deficiency in sport (RED-S) is a condition of low energy availability that has serious long-term consequences on health and sporting performance. Whether intentional or unintentional, the impact of chronic low energy availability was previously described as the `female athlete triad`: low energy availability, amenorrhoea, and low bone density. Oestrogen plays an important role in calcium absorption, hence the link between amenorrhoea and low bone density. However, in 2014, the term RED-S was introduced by the International Olympic Committee (IOC) to reflect research that found much wider consequences across bodily systems, and that the condition affects both male and female athletes. In fact, exercisers of any activity, age group, or level of competition are susceptible to RED-S.